2021
DOI: 10.1002/anie.202112514
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of a Bilayer 2D Supramolecular Organic Framework in Water

Abstract: Accurate control of the layer number of orderly stacked 2D polymers has been an unsettled challenge in selfassembly.H erein we describe the fabrication of ab ilayer 2D supramolecular organic framework from am onolayer 2D supramolecular organic framework in water by utilizing the cooperative coordination of ar od-like bipyridine ligands to zinc porphyrin subunits of the monolayer network. The monolayer supramolecular framework is prepared from the co-assembly of an octacationic zinc porphyrin monomer and cucurb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…A cucurbit[8]­uril (Q[8] or CB[8]) host is a larger homologue of the Q­[ n ]­s family, which not only can accommodate and stabilize V •+ radicals in the confined cavity , but also distinguishes itself by encapsulating V 2+ derivative guests as the electron-accepting moiety and an electron-donating guest to form a host-enhanced charge-transfer complex in its rigid space. In addition, Q[8] as the host can also simultaneously include two homo guests, such as arylpyridinium or naphthalene, which can be dimerized inside the cavity to form highly stable Q[8]-enhanced π–π complexes under the macrocyclic confinement effect. , Evidently, these results indicate that the confined space of the Q[8] cavity has the excellent advantages of strengthening the weak intermolecular interactions and controlling the orientation of the two encapsulated guests. However, to the best of our knowledge, V •+ radicals that are directly triggered by the Q[8]-confined space via intermolecular PET have not yet been studied …”
Section: Introductionmentioning
confidence: 99%
“…A cucurbit[8]­uril (Q[8] or CB[8]) host is a larger homologue of the Q­[ n ]­s family, which not only can accommodate and stabilize V •+ radicals in the confined cavity , but also distinguishes itself by encapsulating V 2+ derivative guests as the electron-accepting moiety and an electron-donating guest to form a host-enhanced charge-transfer complex in its rigid space. In addition, Q[8] as the host can also simultaneously include two homo guests, such as arylpyridinium or naphthalene, which can be dimerized inside the cavity to form highly stable Q[8]-enhanced π–π complexes under the macrocyclic confinement effect. , Evidently, these results indicate that the confined space of the Q[8] cavity has the excellent advantages of strengthening the weak intermolecular interactions and controlling the orientation of the two encapsulated guests. However, to the best of our knowledge, V •+ radicals that are directly triggered by the Q[8]-confined space via intermolecular PET have not yet been studied …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this system represents a formal bilayer with high regularity. In 2021, Yu and co‐workers demonstrated that coordination could be used to guide two 2DSP‐11/CB[8] monolayers to form bilayer structures [13] . In order to achieve this structure, ditopic ligand M15 was prepared to coordinate the zinc porphyrins of the monolayer (Scheme 3).…”
Section: Bilayer 2dp and 2dspmentioning
confidence: 99%
“…In 2021, Yu and co-workers demonstrated that coordination could be used to guide two 2DSP-11/CB [8] monolayers to form bilayer structures. [13] In order to achieve this structure, ditopic ligand M15 was prepared to coordinate the zinc porphyrins of the monolayer (Scheme 3). At a M15/porphyrin ratio of 0.5, the penta-coordination geometry of Zn 2 + enabled selective formation of the corresponding bilayer 2DSP-M11/CB [8] (Figure 1), as was confirmed by AFM investigations.…”
Section: Bilayer 2dp and 2dspmentioning
confidence: 99%
See 2 more Smart Citations